Pengaruh Implementasi Pengembangan Talenta Berbasis Kompetensi Terhadap Kinerja Tenaga Kesehatan di RSUD Kabupaten Mamuju - Rismayanti; Agus Halim (CV. SINAR HOWUHOWU, 2026)
Competency-based talent development is an important way of managing human resources that can improve the performance of employees in the health sector, especially in regional hospitals. Mamuju District Hospital, which is a health referral center in West Sulawesi, must have competent, professional employees who are able to adapt to changes in the health care system. This study aims to analyze the impact of implementing competency-based talent development on the performance of healthcare workers at Mamuju District Hospital. This study uses a qualitative method with a descriptive approach. Informants involved include hospital leaders, department heads, health workers (including doctors, nurses, and other health workers), and HR management staff. Data collection techniques were conducted through in-depth interviews, observation, and document study. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of competency- based talent development has a positive impact on improving the performance of health workers, as seen from improvements in service quality, discipline, professional abilities, and teamwork spirit. However, there are still several obstacles, such as limited funds, heavy workloads, and unequal opportunities for competency development. The conclusion of this study confirms that the development of competency-based talent development has a positive impact on improving the performance of health workers at Mamuju District General Hospital.